I'm stuck with induction problem. Let $0\leq a<b$, prove the next inequality for all $n\in\mathbb{N}$.

$$\frac{b^{n+1}-a^{n+1}}{b-a}<(n+1)b^n$$I need this inequality because with this, we can deduce that the sequence $\left(1+\frac{1}{n} \right)^{n}$ converges.

The base, for $n=1$ it's trivial because $\displaystyle\frac{b^2-a^2}{b-a}=b+a<2b$ because by hypothesis $a<b$. Next suposse that for $n=k$ the inequality holds. If we take the inequality then $$\frac{b^{k+1}-a^{k+1}}{b-a}<(k+1)b^k$$ and multiplying for $b$ in both sides we obtain $$\frac{b^{k+2}-ba^{k+1}}{b-a}<(k+1)b^{k+1}<(k+2)b^{k+1}$$but from here I don't know how to obtain the result. Any hint? Thanks for your help.


Factor out $\frac{b^{n+1}}{b}=b^n$ and get

$$b^n \left(\frac{1-\left(\frac{a}{b}\right)^{n+1}}{1-\frac{a}{b}}\right)=b^n\sum_{k=0}^n\left(\frac{a}{b}\right)^k$$

by the geometric sum formula. Then since $0\leq a<b \implies 0 \leq \frac{a}{b} < 1$ we have for $n>0$

$$b^n\sum_{k=0}^n\left(\frac{a}{b}\right)^k < b^n\sum_{k=0}^n 1 = (n+1)b^n$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.